Elements of ecological economics - Eriksson, Ralf.; Andersson, Jan Otto. (London : Routledge, 2010)
Elements of Ecological Economics provides a comprehensive introduction to the field of ecological economics, an interdisciplinary project trying to give answers to the problems related to the overexploitation of the earth's resources today. These include the problems of global warming (the greenhouse effect) and the overuse of the seas (e.g. overfishing). The book also gives an exposition of the closely related problems of global welfare and justice. The book covers topics including: the general policy perspective required by sustainability economic growth in a historical perspective sustainability conceptions and measurement within ecological economics economics and ethics of climate change global food security the state of the seas on earth and locally (the Baltic Sea).
1. The global ethical trilemma -- 2. Economic growth and human development -- 3. Ethics and ecological economics -- 4. Environmental economics -- 5. Ecological economics: the science of Sustainability -- 6. The Economics and Ethics of Climate Change -- 7. Global food security -- 8. Man and the seas: The oceans and the Baltic Sea -- 9. Growth and degrowth – is another economy possible?
Lisäpainokset: Repr. 2010.
Julkaistu myös verkkoaineistona.
Keywords: Environmental economics; Sustainable development; Climate change; Food supply; miljöekonomi; ympäristötalous; kestävä kehitys; ilmastonmuutokset; ruokaturva; elintarvikehuolto; talouskasvu; ympäristövaikutukset; hållbar utveckling; ekologinen taloustiede